2016
DOI: 10.1002/erv.2472
|View full text |Cite
|
Sign up to set email alerts
|

Enduring Changes in Decision Making in Patients with Full Remission from Anorexia Nervosa

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…Indeed, they indicate that the difference between remitted/recovered AN patients and healthy controls in BMI was larger and with higher variance (as indicated by a larger confidence interval) in studies that used minimal remission criteria (k = 5, Hedges' g = −0. Krawczyk, 2011;Nikendei et al, 2011;Phillips, Jimerson, Pillai, & Wolfe, 2016;Schebendach et al, 2011;Shott, Pryor, Yang, & Frank, 2016;Steward et al, 2016;Tchanturia et al, 2012) or were found to not improve in ED symptoms (Haynos, Roberto, Martinez, Attia, & Fruzzetti, 2014). Sustained weight-restored AN patients did not differ significantly from acutely ill AN patients in body shape dissatisfaction (Harper, Brodrick, Van Enkevort, & McAdams, 2017).…”
Section: Results Of Meta-analysis On Residual Ed Symptomsmentioning
confidence: 95%
See 4 more Smart Citations
“…Indeed, they indicate that the difference between remitted/recovered AN patients and healthy controls in BMI was larger and with higher variance (as indicated by a larger confidence interval) in studies that used minimal remission criteria (k = 5, Hedges' g = −0. Krawczyk, 2011;Nikendei et al, 2011;Phillips, Jimerson, Pillai, & Wolfe, 2016;Schebendach et al, 2011;Shott, Pryor, Yang, & Frank, 2016;Steward et al, 2016;Tchanturia et al, 2012) or were found to not improve in ED symptoms (Haynos, Roberto, Martinez, Attia, & Fruzzetti, 2014). Sustained weight-restored AN patients did not differ significantly from acutely ill AN patients in body shape dissatisfaction (Harper, Brodrick, Van Enkevort, & McAdams, 2017).…”
Section: Results Of Meta-analysis On Residual Ed Symptomsmentioning
confidence: 95%
“…Among ED patients in recovery, results indicated that two cognitive functioning aspects may be deficient: executive functions and emotion regulation processes. In terms of executive functions, AN patients in remission underperformed compared to healthy controls in tasks involving visual perception, decision making, memory, social cognition network, and in set shifting (Holliday, Tchanturia, Landau, Collier, & Treasure, 2005;Buehren et al, 2011;McAdams & Krawczyk, 2011: Danner et al, 2012Heled, Hoofien, Bachner-Melman, Bachar, & Ebstein, 2014;Lindner et al, 2014;Talbot et al, 2015;Steward et al, 2016) or showed no significant change after recovery (Bodell et al, 2014;Nikendei et al, 2011). Moreover, specifically in decision making, partially remitted AN patients were impaired compared to healthy controls (Steward et al, 2016).…”
Section: Cognitive Functioningmentioning
confidence: 90%
See 3 more Smart Citations